2010
DOI: 10.1088/0957-4484/21/50/505704
|View full text |Cite
|
Sign up to set email alerts
|

Single-crystalline Ni2Ge/Ge/Ni2Ge nanowire heterostructure transistors

Abstract: In this study, we report on the formation of a single-crystalline Ni(2)Ge/Ge/Ni(2)Ge nanowire heterostructure and its field effect characteristics by controlled reaction between a supercritical fluid-liquid-solid (SFLS) synthesized Ge nanowire and Ni metal contacts. Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies reveal a wide temperature range to convert the Ge nanowire to single-crystalline Ni(2)Ge by a thermal diffusion process. The maximum current density of the fully … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 32 publications
3
50
1
Order By: Relevance
“…2). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies revealed a wide range of annealing temperature, from 400 to 500°C, to drive Ni diffusion into the Ge nanowire and to form single-crystalline Ni2Ge [2]. The formed Ni2Ge has an orthorhombic crystal structure (space group 62) with the set of lattice constants: a = 0.511 run, b = 0.383 nm, and c = 0.726 nm.…”
Section: Results An D Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2). Scanning electron microscopy (SEM) and transmission electron microscopy (TEM) studies revealed a wide range of annealing temperature, from 400 to 500°C, to drive Ni diffusion into the Ge nanowire and to form single-crystalline Ni2Ge [2]. The formed Ni2Ge has an orthorhombic crystal structure (space group 62) with the set of lattice constants: a = 0.511 run, b = 0.383 nm, and c = 0.726 nm.…”
Section: Results An D Discussionmentioning
confidence: 99%
“…I N the effort of making high-quality nanoscale source/drain contacts to a semiconductor nanowire channel, one attractive strategy is to use thermal annealing to promote the solid-state reaction of metal contacts with semiconductor nanowires [1][2][3][4][5][6]. In the metal-Si(Ge) nanowire system, the produced silicide(germanide) region after annealing can be used as Schottky source/drain contacts for the fabrication of Si(Ge) nanowire transistors.…”
Section: Introductionmentioning
confidence: 99%
“…2(b). 22,[44][45][46][47] For example, Fig. For Ge/Si nanowires, however, the 1-D germanidation/silicidation with rapid thermal 90 annealing (RTA) has been extensively studied to produce singlecrystalline germanide/silicide contacts with atomically clean interfaces.…”
Section: Electrical Spin Transport In Semiconductor Bulk and Thin Filmentioning
confidence: 99%
“…where P J is the spin polarization of the current injected from 45 the spin injector into the semiconductor channel, is the spin diffusion length, is the semiconductor conductivity, A is the semiconductor channel cross-sectional area, and L is the spatial distance between the spin injector and detector. The ( sign denotes the parallel (anti-parallel) magnetization state for the spin 50 injector and detector.…”
Section: Electrical Characterization Of Spin Transportmentioning
confidence: 99%
See 1 more Smart Citation